Safety and Efficacy of Autologous Platelet-rich Fibrin on Graft Uptake in Myringoplasty: A Randomized Controlled Trial - Nair,Nithin Prakasan (2019)
Abstract Introduction Chronic suppurative otitis media is a common ailment in developing countries, and it generally presents with otorrhea and hearing loss. Different surgical procedures have been used to treat otitis media; among them is myringoplasty, which is a procedure that includes repair of the tympanic membrane. Platelet concentrates have been used widely in different types of wounds and are found to improve wound healing. Hence, the use of platelet-rich fibrin in myringoplasty will also improve the tympanic membrane healing. Objectives To assess the safety and efficacy of autologous platelet-rich fibrin on graft uptake in myringoplasty. Methods Eighty-six patients were observed during the study period of two years. Forty-three patients in the study group underwent myringoplasty aided with plateletrich fibrin, and 43 patients in the control group went through the same procedure but without the platelet-rich fibrin. The patients were observed for three months postoperatively by a blinded observer. Results A total of 4.7% of the patients in the study group had postoperative infection, compared with a rate of 19% in the control group (p = 0.039). The graft uptake success rate was found to be 97.7% in the study group as compared with 81% in control group (p = 0.012). The results were found to be statistically significant. Conclusion Being autologous in nature, and by comparing the groups, platelet-rich fibrin is safe for patients. The postoperative graft uptake rate is better in cases in which plateletrich fibrin was used. The postoperative infection rate was also lower in the same group.